Methodology for assessing the prevalence of angina in primary care using practice based information in northern England. Issue 1 (February 1997) - Bottomley, A
Abstract : OBJECTIVES: The study aimed to consider the value of nitrate prescriptions issued by general practices as an indicator of coronary heart disease and to compare this with the use of coronary heart disease registers. DESIGN: The study was a cross sectional survey. A self completed questionnaire was used by general practices to indicate an age and gender breakdown of the total practice population, the number of patients taking nitrates, and details of patients recorded on a coronary heart disease register. SUBJECTS: All 48 general practices registered with Wakefield Family Health Services Authority were sent a questionnaire. MAIN RESULTS: The prevalence of angina in the sample population of 164796 was 3.1%. The prevalence of angina as assessed by coronary heart disease registers was significantly higher at 4.3%. CONCLUSIONS: Using questionnaires to assess how many patients are taking nitrates and therefore have angina may provide a quick, "snapshot" view of the prevalence of angina but the methodology is not a robust epidemiological tool. It is likely to provide errors in estimates of true prevalence and risks some under estimation when compared with coronary heart disease registers.